Morfogênese de gramíneas nativas do Rio Grande do Sul (Brasil) submetidas a pastoreio rotativo - Santos, Aline Bosak dos (2012)
The knowledge of plants response to grazing, with emphasis on growing and senescence processes is necessary to improve the natural grasslands usage and efficiency. Based on this, this work aimed to study morphogenic characteristics of predominant natural grasses in the central region Rio Grande do Sul State (RS), under rotational grazing based on thermal time intervals. The study was carried out at Universidade Federal de Santa Maria area, in Santa Maria/RS city, from September 2010 to March 2011, in a completely randomized experimental design, with two treatments: 375 degree day and 750 degree day grazing intervals and three repetitions. Morphogenic characteristics were measured on Andropogon lateralis Nees, Aristida laevis Nees, Axonopus affinis Chase, Paspalum notatum Fluegge and Paspalum plicatulum Michx. grass species, chosen based on functional typology. There was no significant difference between the treatments, but it was verified among species and seasons. The largest leaf appearance rates, and the the smallest leaf appearance intervals, were observed on P. notatum and A. affinis species. A. laevis e P. plicatulum showed the largest leaf lifespan and leaf elongation rate. Spring is characterized as the growing season, with highest leaf appearance and elongation values, and summer is marked by the flowering initiation, represented by internodes elongation and reduction of morphogenic characteristics. P. notatum is the grazing species with the greatest adaptative potential.